Sosialisasi Keamanan Pangan Untuk UKM Pangan Industri Rumah Tangga Centra Kuliner Di Kabupaten Aceh Besar - Manovri Yeni; Emmi Suryani; Ira Dama Yanti; Susanti Susanti (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
SME in Aceh Besar District, especially those who are engaged in the culinary sector currently still have various problems in developing their business, which one of the problem is related to food safety, namely those relating to good processed food production (CPPOB), Good Manufacturing Practice (GMP) as well as Processed Food Label Standards. If SMEs have fulfilled all of these three things, then they can apply for a Certificate of Food Production - Home Industry (SPP-IRT), one of which functions as a marketing permit for SME products. In preparation for obtaining the SPP-PIRT, socialization is needed so that SMEs really understand and can prepare themselves early, so it will be easier to follow the procedures and requirements given based on existing provisions. The socialization activities were considered successful and useful, the participants' level of understanding about food safety increased from 54% to 80% as evidenced by the results of the pre-test and post-test. For follow-up socialization activities, on average, participants need a maximum of one month to repair existing product deficiencies. And all participants will receive recommendations to take part in food counseling in order to quickly get SPP-PIRT from the Aceh Besar district health office.